Detect Heat Shock Protein 70 and Tumor Necrosis Factor Alpha in Obese Breast Cancer Patients - Moaed E. Al-Gazally; Alaa S. Al-Awad; Sheerin H. Abbas (Journal of Global Pharma Technology, 2017)
This study include the measurement of heat shock protein 70 (Hsp 70) and tumor necrosis factor alpha (TNF-α) in breast cancer(BC) by Enzyme-linked immunosorbent assay(ELISA) method. In addition, study the relationship between both (HSP-70 and TNF-α) with obesity≥ 30 Kg/M2 for patients (No.58) and controls (No.30) with age (20-50 years).Hsp-70 elevated while TNF-α decreased in obese BC patients. BC incidence is very low before age 25 and increases in age up 40 years. Increasing of BMI lead to increasing in the breast cancer incidence. Result Hsp-70 elevated statically significant where mean of Hsp-70(56.32 ± SD =18.78, p-value= 0.0001) while TNF-α decreased significantly where mean of TNF-α (163.81pg/ml ± SD = 64.94, p-value= 0.0001) in obese BC patients. The concentration of TNF insignificant decreased where), there is significant the obesity significant with BC patients (p-value = 0.048).Conclusion: Obesity is risk factor for BC. Concentration of Hsp-70increased while TNF-α decreased after Chemotherapy.